Respuesta :

Answer:

n = 9

Step-by-step explanation:

Here we have the table:

X     Y

4     3

6    5

7     6

10   n

First, we want to find the rule.

in the first pair we have:

x = 4

y = 3

We can see that the y-value is one smaller than the x-value

y = 3 = 4 - 1 = x - 1

For the second pair we have:

x = 6, y = 5

We again can see that the y-value is one smaller than the x-value

y = 5 = 6 - 1 = x - 1

For the third pair we have:

x = 7, y = 6

Again, can see that the y-value is one smaller than the x-value.

y = 6 = 7 - 1 = x - 1

We can conclude that the rule is:

y = x - 1

For the last pair, we have:

x = 10, y = n

Then:

n = 10 - 1 = 9

n = 9

Then the table is:

X     Y

4     3

6    5

7     6

10   9